DETERMINATION OF THE SEROPREVALENCE OF IgG ANTIBODIES AGAINST MEASLES VIRUS AMONG MEDICAL STUDENTS IN BELGRADE - Stojakovic, Nikola (Medicinski podmladak, 2026)
Introduction: The measles virus is a negative-sense single-stranded RNA virus belonging to the family Paramyxoviridae. It causes measles, also known as rubeola or childhood rash fever. Before the introduction of mandatory vaccination, around 2 million people worldwide died from this disease annually. However, with the implementation of the MMR (measles, mumps, and rubella) live attenuated vaccine, that number has dropped to around 100 thousand deaths per year. The Aim: The aim of this study was to determine the seroprevalence of antibodies against the measles virus in the population of medical students at the University of Belgrade. Material and Methods: In the study, sera of 99 voluntarily enrolled students from the Faculty of Medicine, University of Belgrade, were examined. Commercial ELISA kits from Euroimmun Medical Diagnostics (Lübeck, Germany) were used according to the manufacturer’s instructions. Data obtained from an anonymous survey were also analyzed. Normality of distribution was evaluated using mathematical methods (coefficient of variation, Shapiro-Wilk test) and graphical methods (histogram and boxplot). Results: In our study, 92 out of 99 participants (93%) reported being vaccinated with the MMR vaccine. Thirteen students reported having had measles, while positive antibodies were confirmed in 89% of the participants. The application of statistical tests did not prove a significant difference in the representation of positive findings between genders, or between persons who attended preschool institutions compared to those who did not. Conclusion: The study’s results demonstrated the seroprevalence of antibodies to the Measles virus in medical students aged 19 to 29 years. The lack of seroconversion in 4% of the vaccinated population can be considered an indication for the introduction of an additional dose of measles vaccine in this population.